The Influence of Microfinance Institutions on Nigerian Small, Micro, And Medium Enterprises - SHUMBA, KNOWLEDGE; Ekpo, Victor; Ebewo, Patrick (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Poverty is a significant concern in most countries, including Nigeria, which has been dubbed the world's poverty capital. Most developing countries regard small, micro, and medium-sized companies (SMMEs) as a sure strategy to reduce poverty by lowering a country's unemployment rate. Microfinance institutions (MFIs), especially banks, were commissioned by the Central Bank of Nigeria (CBN) to cater to self-employed people and businesses. There is compelling evidence that MFIs are not doing enough and are failing to fulfill their mandate. As a result, this paper sought to investigate the impact MFIs have on SMMEs in Nigeria. Design/methodology/approach: This descriptive study, made use of a convenience sample strategy to collect survey data from 384 SMMEs in two Nigerian states: Abuja and Nasarawa. Data was collected from 350 respondents. Findings: The findings showed that MFIs significantly influenced SMMEs regarding technology transfer and financial services and aided SMME (small, medium, and micro enterprises) growth. MFIs in Nigeria are ineffective in offering the services of aspects of facilitator of SMEs growth, tool for social change, provider of banking services to the people and transferor of technology. Practical implications: The CBN should make sure that MFIs, especially the banks focus more on servicing SMMEs. MFIs should do more in the areas of sensitiation and tailor their products to suit their customer base. Originality/value: There are limited studies on the Nigerian context for SMMEs and MFIs.